1992
DOI: 10.1002/fedr.19921030124
|View full text |Cite
|
Sign up to set email alerts
|

Additional notes to the checklist of Cuban cultivated plants (2)

Abstract: Checklists are considered as useful tools for exploration work in plant genetic resources programmes. New information is presented for the checklist of Cuban cultivated plants (ESQUIVEL et al. 1989). 107 species were newly included. For a few other species additional data are given. This information is the result of two further collecting missions in Cuba. Fodder crops predominate, as a result of the cooperation with a specialist in this field. A computerized database was developed allowing not only to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…3 Haitian informant with Artemisia absinthium in his homegarden coins) at its base to ensure that its medicinal properties will be effective. Although Hammer et al (1990) citing Fuentes (1988) reported that A. absinthium is frequently grown in Cuban homegardens as a condiment and medicinal plant, it is currently very difficult to find, at least in the province of Camagüey. Also, the plant is either absent or cited only causally in the most important treatises on Cuban folk medicine (Roig 1974;Seoane 1984) and in the ethnomedical studies in the Province of Camagüey (Beyra et al 2004).…”
Section: Traditional Ethnobotanical Knowledgementioning
confidence: 99%
“…3 Haitian informant with Artemisia absinthium in his homegarden coins) at its base to ensure that its medicinal properties will be effective. Although Hammer et al (1990) citing Fuentes (1988) reported that A. absinthium is frequently grown in Cuban homegardens as a condiment and medicinal plant, it is currently very difficult to find, at least in the province of Camagüey. Also, the plant is either absent or cited only causally in the most important treatises on Cuban folk medicine (Roig 1974;Seoane 1984) and in the ethnomedical studies in the Province of Camagüey (Beyra et al 2004).…”
Section: Traditional Ethnobotanical Knowledgementioning
confidence: 99%